2014
DOI: 10.3906/vet-1304-43
|View full text |Cite
|
Sign up to set email alerts
|

The results of consecutive superovulations in cows by induction with various exogenous progesterone routes

Abstract: Nafion, a sulfonated tetrafluoroethylene copolymer, consists of a hydrophobic fluorocarbon backbone (-CF2-CF2-) to which hydrophilic sulfonate groups ( SO −3 ) are attached. The presence of negatively charged sulfonate groups in a nanomembrane brings about a high level of proton conductivity. In this study, Saccharomyces cerevisiae was used for production of bioelectricity in a 2-chambered microbial fuel cell (MFC). We selected 9-cm 2 Nafion 117 and Nafion 112 as nanomembranes to transport the produced proton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…Betterridge (1997) reported that the unusual endocrine conditions after superovulation adversely affect embryo recovery and viability, and embryo recovery rates would decrease over time after ovulation. The embryo recovery rates achieved in the present study were lower than those reported in some other studies (Bülbül et al 2010;Akyol et al 2014;Hussein et al 2014;Karaşahin et al 2016). Kanagawa et al (1995) reported that the differences in embryo recovery rates between studies were related to factors such as washing time, washing media and washing number, catheter type and positioning of the catheter, technician experiences, etc.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Betterridge (1997) reported that the unusual endocrine conditions after superovulation adversely affect embryo recovery and viability, and embryo recovery rates would decrease over time after ovulation. The embryo recovery rates achieved in the present study were lower than those reported in some other studies (Bülbül et al 2010;Akyol et al 2014;Hussein et al 2014;Karaşahin et al 2016). Kanagawa et al (1995) reported that the differences in embryo recovery rates between studies were related to factors such as washing time, washing media and washing number, catheter type and positioning of the catheter, technician experiences, etc.…”
Section: Discussioncontrasting
confidence: 78%
“…The main factor, which limits the extensive use of embryo transfer in cattle, is the unpredictability and variability of the superovulatory response (Kafi and McGowan 1997;Vieira et al 2014). Several factors, including among others, age, breed, season, nutrition, individual response, type of gonadotropin used, subclinical infection and lactation, affect the response of cows to superovulation (Kafi and McGowan 1997;Akyol et al 2014;Mikkola et al 2019). In their study, in which they compared different progesterone treatment regimens in Holstein Friesian cows and applied a 4 day-superovulation scheme based on the administration of decreasing FSH doses given twice a day, Akyol et al (2014) determined the mean CL number as 4.82±0.29 in the group that was applied progesterone-releasing intravaginal devices (PRID) and as 6.71±0.29 in the group that was applied ear implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation